Facilitative interpersonal skills performance test: Psychometric analysis of a German language version. Issue 12 (6th August 2019) - Munder, Thomas; Schlipfenbacher, Carina; Toussaint, Kyra; Warmuth, Mirjam; Anderson, Timothy; Gumz, Antje
Abstract: Objective: This study aimed at a psychometric analysis of the Facilitative Interpersonal Skills (FIS) performance test, a test of therapist relational skills that has repeatedly been found to predict psychotherapy outcome. We investigated the reliability, unidimensionality, and convergent validity of a German language version and psychometrics relevant for repeated and short assessments. Method: Thirty‐nine trainee therapists took the FIS performance test and responded to self‐report scales. Results: Inter‐rater agreement and internal consistency were high. The findings suggest that the FIS is a unidimensional scale. Correlations between the FIS and self‐reported social skills, interpersonal problems, and working involvement were absent to low. FIS performance was independent from specific video stimuli and there was no indication of temporal effects. Conclusions: The findings suggest that the FIS is robust and ready to be used in repeated assessments and in short form. Further conceptual clarification of the FIS is needed.